Quantification of body iron and iron absorption in the REDS‐II Donor Iron Status Evaluation (RISE) study. Issue 7 (19th May 2017) - Kiss, Joseph E.; Birch, Rebecca J.; Steele, Whitney R.; Wright, David J.; Cable, Ritchard G.
Abstract : BACKGROUND: Repeated blood donation alters the iron balance of blood donors. We quantified these effects by analyzing changes in body iron as well as calculating iron absorbed per day for donors enrolled in a prospective study. STUDY DESIGN AND METHODS: For 1308 donors who completed a final study visit, we calculated total body iron at the enrollment and final visits and the change in total body iron over the course of the study. Taking into account iron lost from blood donations during the study and obligate losses, we also calculated the average amount of iron absorbed per day. RESULTS: First‐time/reactivated donors at enrollment had iron stores comparable to previous general population estimates. Repeat donors had greater donation intensity and greater mean iron losses than first‐time/reactivated donors, yet they had little change in total body iron over the study period, whereas first‐time/reactivated donors had an average 35% drop. There was higher estimated iron absorption in the repeat donors (men: 4.49 mg/day [95% confidence interval [CI], 4.41‐4.58 mg/day]; women: 3.75 mg/day [95% CI, 3.67‐3.84 mg/day]) compared with estimated iron absorption in first‐time/reactivated donors (men: 2.89 mg/day [95% CI, 2.75‐3.04 mg/day]; women: 2.76 mg/day [95% CI, 2.64‐2.87 mg/day]). The threshold for negative estimated iron stores (below "0" mg/kg stores) was correlated with the development of anemia at a plasma ferritin value of 10 ng/mL. CONCLUSIONS: These analyses provide quantitative data on changes in estimated total body iron for a broad spectrum of blood donors. In contrast to using ferritin alone, this model allows assessment of the iron content of red blood cells and the degree of both iron surplus and depletion over time.